Winter and Spring insights into physical drivers of iron supply to the mixed layer in the South Atlantic sector of the Southern Ocean - Sitofile, Miranda (Stellenbosch : Stellenbosch University, 2026)
Thesis (MSc)--Stellenbosch University, 2025.